Ablation of hephaestin and ceruloplasmin results in iron accumulation in adipocytes and type 2 diabetes. Issue 3 (31st January 2018) - Zheng, Jiashuo; Chen, Min; Liu, Guohao; Xu, En; Chen, Huijun
Abstract : Little is known about the iron efflux mechanism in adipocytes. Here, we used hephaestin ( Heph ) and ceruloplasmin ( Cp ) single‐knockout (KO) mice and Heph/Cp double‐KO mice to investigate the roles of multicopper ferroxidases (MCFs) in this process. We show that both HEPH and CP are expressed in subcutaneous adipose tissue. Ablation of either MCF leads to a compensatory increase in the other, which contributes to the balance of iron status. However, ablation of both MCFs together induces severe iron deposition in adipocytes which is associated with decreased adiponectin and leptin mRNA expression. Furthermore, Heph/Cp KO mice display disordered carbohydrate metabolism characterized as type 2 diabetes. Together, these results demonstrate the protective roles of HEPH and CP in preventing iron overload in adipocytes. Abstract :